Curriculum content mapping of the Chinese National Biology Curriculum Standards for middle school: an analysis from the OECD Education 2030 perspective - Shan Lin; Jian Wang; Xiaorong Li; Xingdong Tang; Chang Sun; Mingxia Tan; Tian Luo (Disciplinary and Interdisciplinary Science Education Research, 2023)
Abstract Curriculum standards are a critical component of a nation’s educational system and directly impact talent development and overall national development. Most studies on curriculum standards focus on a single competency. This study aims to understand the extent to which the competencies outlined in the OECD 2030-oriented learning framework are reflected in China’s compulsory education biology curriculum as a whole and within individual content subjects. In this study, we conducted a content analysis of China’s National Biology Curriculum Standards (Grades 7–9). The result shows that the standards cover 20 of the 28 competencies, focusing on foundational literacies, transformative competencies and competency development. We found that certain competencies, such as Action, Literacy, and Problem-solving, were emphasized across content subjects, while other competencies were uniquely emphasized within specific content subjects. This study provides a comprehensive view of China’s National Biology Curriculum Standards (Grades 7–9) from the perspective of future literacy development and can inform efforts to reform the curriculum.